Factors Affecting Pre-Hospital and In-Hospital Delays in Treatment of Ischemic Stroke; a Prospective Cohort Study - Ghadimi, Neda; Hanifi, Nasrin; Dinmohammadi, Mohammadreza (Archives of Academic Emergency Medicine, 2021)
Introducion: The outcomes of acute ischemic stroke (AIS) are highly affected by time-to-treatment. The present study aimed to determine the factors affecting in-hospital and pre-hospital delays in treatmentof AIS. Methods: This prospective study was carried out on 204 AIS patients referring to the stroke care unit in Zanjan (Iran) in 2019. The required data were collected by interviewing the patients and families and using patients’ records and observations. Results: The maximum delay was related to onset-to-arrival time (288.19 ± 339.02 minutes). The logistic regression analysis indicated a statistically significant decline in the treatment delay via consultation after the initiation of symptoms (p< 0.001), transferring the patient through emergency medical service to the hospital (p<0.001), and patients’ perception regarding AIS symptoms (P< 0.001). Conclusion: It is essential to inform people regarding AIS symptoms and referring to AIS treatment units to reduce the treatment time.